Quality assessment of clinical guidelines in the care of laryngitis and pharyngitis according to AGREE II - Lucas Mateus Rodrigues Carvalho; Ana Paula de Oliveira Barbosa; Nara Amanda Laismann; Débora Santos Lula Barros; Rodrigo Fonseca Lima; Rafael Santos Santana (CoDAS)
ABSTRACT Purpose The study aimed to identify and assess the methodological quality of essential clinical guidelines for the management of laryngitis and pharyngitis. Methods A systematic search of clinical guidelines for the management of laryngitis and pharyngitis was performed in three databases. Methodological quality was assessed according to AGREE II, in which each item in its domains was scored by four independent evaluators. To determine the agreement, a weighted Kappa square statistic calculation was performed. Results 81 studies were found in the bibliographic sources consulted and all were evaluated. Considering the exclusion criteria, seven guidelines were selected for final evaluation by AGREE II. The squared weighted Kappa coefficient calculated after the first round of evaluation by AGREE II was 0.85, within an almost perfect agreement rate. The domains “stakeholder engagement”, “applicability”, and “editorial independence” had the lowest mean scores and the highest standard deviation indices. They had, respectively, a mean score of (63.7%) with a standard deviation of (17%), a mean score of (65.7%) with a standard deviation of (22%), and a mean score of (35%) with a standard deviation of (23%). The use of penicillin, erythromycin, ampicillin, amoxicillin, azithromycin and clarithromycin were recommended in (75%) of all guidelines that presented pharmacological measures. As a non-pharmacological measure, oral rehydration and gargling were recommended by two guidelines. Conclusion The statistical results indicate that all guidelines were considered as recommended. However, no uniformity was observed in the recommendations of these seven guidelines with regard to non-pharmacological and pharmacological treatment.